The Supply Side of Second-Order Elections in the Czech Republic: A Light at the End of the Tunnel? - Jan Kovar (Romanian Journal of European Affairs, 2013)
This paper attempts to contribute to the debate on the Europeanization of European Parliament elections. Because these elections are supposedly fought over national political issues, the analysis focuses on one aspect of political parties’ supply for these elections, namely their election programmes. To this aim, a content analysis is conducted, within a comparative framework, of selected Czech political parties’ programmatic documents. At the same time, the question is asked: to what extent do these programmes offer EU-level solutions—in other words, in terms of issues, does Europeanization or domestication prevail in the manifestos? The results show that parties focus on EU issues in their Euro manifestos and feature an apparent degree of Europeanization of this part of their supply for EP elections. From this perspective, these results can be considered a light at the end of the (second-order) tunnel, given that at least the programmatic part of parties’ supply is about European integration after all.